The Effects of the World Economic Crisis on Manager Compensation - Deli\(\acute{c}\), Adisa; Nuhanovi\(\acute{c}\), Amra (Current Topics on Business, Economics and Finance Vol. 5, 2023)
Most economists who studied the financial crises in the middle of the 1980s came to the conclusion that a significant number of them were caused by a confluence of bad macroeconomic policies and unfavorable external shocks that led to deficits in many countries' current accounts and balance of payments. In the last few years, a lot of has been written about the global financial crisis. In these scientific discussions, the basic factors of that crisis are often analyzed. All these analyzed factors made the financial crisis more long-term, more difficult, uncertain and with difficult to foresee consequences. On the other hand, understanding the causes and preventing the consequences of crises are an essential prerequisite for the economic and social progress of a country. In this regard, the main goal of the research was based on an attempt to explain the point of view that the greed of Wall Street bankers (caused by excessively high managerial compensations), is one of the important factors in the deepening of the world financial crisis. The study also presents an overview of the possible directions of regulation on managerial compensation, all with the aim of suppressing larger-scale crises in the near future. Finally, in order to complete the research, the authors analyzed the situation in the field of managerial compensation in Bosnia and Herzegovina. The introduction of ethical conduct in the management payment compensation is also an important issue requiring more studious approach in the forthcoming period.